2020
DOI: 10.3390/psych2040016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Stress during Pregnancy on Child’s Neurodevelopment

Abstract: (1) Background: High stress levels during pregnancy can affect the organogenesis and the foetus’ central nervous system maturation. The objective of this study was to determine whether a relationship between maternal stress during pregnancy and alterations in child neurodevelopment exists; (2) Methods: A bibliographical review was carried out following PRISMA Methodology and using Scopus, Web of Science and Cinahl databases. The research questions were made using PEO methodology (Participants, Exposition, Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Whether increased psychological distress is transient or persistent, and whether and how it affects the future generation remains to be determined.Pregnancy involves profound physiological and psychological changes in women 1-3 , due to the hormonal and biological changes in the body 4,5 , and due to the surrounding context 6,7 . These changes have been associated to elevated prenatal symptoms of anxiety and depression [8][9][10] , which in turn are related to poor outcomes in the offspring [11][12][13] . Accordingly, pregnant women's known vulnerability for anxiety and depression has become a concern during the COVID-19 pandemic and the severe lockdown measures, including social distancing, workrelated changes, and limited access to healthcare services 14 .…”
mentioning
confidence: 99%
“…Whether increased psychological distress is transient or persistent, and whether and how it affects the future generation remains to be determined.Pregnancy involves profound physiological and psychological changes in women 1-3 , due to the hormonal and biological changes in the body 4,5 , and due to the surrounding context 6,7 . These changes have been associated to elevated prenatal symptoms of anxiety and depression [8][9][10] , which in turn are related to poor outcomes in the offspring [11][12][13] . Accordingly, pregnant women's known vulnerability for anxiety and depression has become a concern during the COVID-19 pandemic and the severe lockdown measures, including social distancing, workrelated changes, and limited access to healthcare services 14 .…”
mentioning
confidence: 99%
“…Around 78% of women have moderate stress during pregnancy, while 6% have severe stress. 3 A previous study showed that 54% of the mothers who had stress during pregnancy finally had preterm birth, while the percentage of all mothers with preterm bith was 23%. 4 The term birth occurs between 37 and 42 weeks, while preterm birth is defined as delivery before 37 weeks gestation age.…”
Section: Introductionmentioning
confidence: 97%